Development, Synthesis, and in silico Investigations of Novel Acyclic Allyl Fluoride Derivatives - Chauhan, Nishita; Singh, Harjinder; Singh, Kamal Nain; McKenna, Jeffrey M.; Saini, Vaneet (Synthesis, 2022)
A one step electrophilic fluorination of alkenes is reported, which furnishes the products in a highly regioselective manner via allylic rearrangement. The reaction proceeds efficiently under mild conditions with the use of trisubstituted alkenes as olefin partner and Selectfluor as an electrophilic fluorinating agent without the need of any transition metal catalyst or pre-functionalized substrates. Virtual screening of the newly synthesized compounds shows their potential application as herbicides by inhibiting protoporphyrinogen oxidase (PPO) enzyme.
Keywords: fluorination; metal-free; Selectfluor; organic synthesis; molecular docking; herbicides